(untitled) (LEARNing Landscapes, 2015)
Through the use of personal anecdotes drawn from a long career as a professional educator, the author contends that professional development for professional educators is not just an isolated "quick fix" program now and then, or a series of performance-focused activities, but rather, professional learning opportunities exist in multiple, diverse, and occasionally in unusual and unexpected situations and contexts throughout one’s career. He suggests that what all teachers and school leaders require for professional learning to flourish is both time and space, a clear sense of purpose based on student learning, learning opportunities that are appropriate to roles and career stage, and the support and trust from leadership both inside and outside of schools and districts. It is professional learning, not tests, targets, or performance training, that increases students’ learning.